Sawdust-Derived Activated Carbon with Hierarchical Pores for High-Performance Symmetric Supercapacitors - Yan Zhou; Jun Li; Shilin Hu; Gujie Qian; Juanjuan Shi; Shengyun Zhao; Yulin Wang; Chuan Wang; Jiabiao Lian (Nanomaterials, 2022)
The recyclable utilization of waste biomass is increasingly important for the development of a sustainable society. Here, the sawdust-derived activated carbon (SD-AC) has been prepared via a convenient H3PO4-based activation method and further trialed as an electrode for use as a high-performance symmetric supercapacitor. The as-prepared SD-AC possesses a hierarchically porous structure with micropores (0.55 nm) and mesopores (2.58 nm), accounting for its high specific surface area of 621 m2 g−1, with a pore volume of 0.35 cm3 g−1. Such a hierarchically porous structure can offer a favorable pathway for fast ion penetration and transportation, enhancing its electrochemical performance. As a result, the SD-AC electrode exhibits a maximum specific capacitance of up to 244.1 F g−1 at 1.0 A g−1, a high rate capability (129.06 F g−1 at 20 A g−1), and an excellent cycling performance, with 87% retention over 10,000 cycles at 10 A g−1. Of particular note is that the SD-AC-based symmetric supercapacitor achieves a maximum energy density of 19.9 Wh kg−1 at the power density of 650 W kg−1, with a long-term cycle lifespan. This work showcases the recyclable utilization of waste biomass for the preparation of high-value activated carbon for efficient energy storage.